Essays on Life, Art and Science - Butler, Samuel, 1835-1902; Streatfeild, R. A. (Richard Alexander), 1866-1919 (Salt Lake City, UT : Project Gutenberg, 2002)
"Essays on Life, Art and Science" by Samuel Butler is a collection of essays written in the late 19th century. This anthology illustrates Butler's remarkable versatility and wit as he explores a variety of subjects, ranging from personal reflections to critiques of societal norms, art, and scientific thought. The collection contains insights into Butler's philosophical musings, personal experiences, and critical observations on human behavior and the nature of existence. The opening of the essays introduces readers to Butler's thoughts on life and literature, highlighting his self-deprecating humor and unique perspective on writing. He begins by sharing a personal anecdote about his search for a suitable writing desk in the British Museum, revealing his introspective nature and the struggle he faces as an author. This opening sets the tone for the essays that follow, as Butler reflects on various literary figures, articulating complex ideas in a relatable manner while drawing connections between himself, his writing, and the legacy of influential writers throughout history. The result is a captivating exploration of art, philosophy, and the intricacies of life that invites readers to contemplate their own existence and the world around them. (This is an automatically generated summary.)
Introduction -- Quis desiderio...? -- Ramblings in Cheapside -- The aunt, the nieces and the dog -- How to make the best of life -- The sanctuary of Montrigone -- A medieval girl school -- Art in the valley of Saas -- Thought and language -- The deadlock in Darwinism.
Release date is 2002-10-01
Transcribed from the 1908 A. C. Fifield edition by David Price
Keywords: Science; Evolution; Art criticism